APPLICATION OF INTERNET OF THINGS TECHNOLOGY IN MODERN THEATRE ARTS TO ENHANCE BRAND IMAGE - Franciakus Antonius Alijoyo; Hermansyah; Safina Meilia (Adisam Publisher, 2025)
Theatrical arts have been an important part of human culture for centuries and have been able to improve the image of the theatre arts community in this modern era. This research focuses on Internet of Things (IoT) technology as a bridge for innovation in theatre arts, especially in increasing the interest on visiting theatre arts performances in Bandung. The author will discuss how the application of IoT technology has changed the way we understand, create, and enjoy theatre arts, and how IoT technology provides the ability to integrate various elements in theatre productions, including lighting, sound, special effects, and interaction, thereby increasing audience interest. This study uses a quantitative approach with mediating variables and uses a Structural Equation Model (SEM) to test direct and indirect effects. The population was not specified but the sample was at least 200 respondents. The research was conducted from September to November 2023 on potential audiences or connoisseurs of performing arts but never watched theatre arts, especially at the Baraya Theatre Community in Bandung City with a focus on brand image, consumer interest, and the use of IoT in theatrical performances